2019
DOI: 10.3390/antiox9010027
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Cornus officinalis on Stress-Induced Hippocampal Deficits in Rats and H2O2-Induced Neurotoxicity in SH-SY5Y Neuroblastoma Cells

Abstract: Oxidative stress plays a vital role in neurodegenerative diseases. Cornus officinalis (CC) has a wide range of pharmacological activities (e.g., antioxidant, neuroprotective, and anti-inflammatory). The present study was undertaken to elucidate the neuroprotective mechanism of CC and fermented CC (FCC) on stress and H2O2-induced oxidative stress damage in rats and SH-SY5Y cells. A dose of 100 mg/kg CC or FCC was orally administered to rats 1 h prior to immobilization 2 h per day for 14 days. CC, especially FCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 54 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Cornus officinalis (CO) of the dogwood genus has been found in Eastern Asia for more than 2000 years and has been employed as a traditional natural product for maintaining liver and kidney health [ 20 ]. Manu et al have indicated the beneficial effects of CO on type 2 diabetes, neuroinflammation, and bone loss [ 21 , 22 , 23 , 24 ]. Recent studies have shown that the CO extract possesses potent anti-inflammatory action against oxidative stress in RAW 264.7 cells and decreases proinflammatory factors, such as IL-1β, interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α), in numerous types of inflammation [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cornus officinalis (CO) of the dogwood genus has been found in Eastern Asia for more than 2000 years and has been employed as a traditional natural product for maintaining liver and kidney health [ 20 ]. Manu et al have indicated the beneficial effects of CO on type 2 diabetes, neuroinflammation, and bone loss [ 21 , 22 , 23 , 24 ]. Recent studies have shown that the CO extract possesses potent anti-inflammatory action against oxidative stress in RAW 264.7 cells and decreases proinflammatory factors, such as IL-1β, interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α), in numerous types of inflammation [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cornus officinalis (CO) has been widely used as a commercialized raw material for tea and health supplements as an herbal medicine [23]. Many studies demonstrate protective effects of CO on hepatitis, osteoporosis, oxidative stress and obesity [24][25][26]. Ribes fasciculatum (RF) is also a common alternative traditional medication against inflammatory conditions such as allergy, aging and autoimmunity in Asia [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Shan-Zhu-Yu extract can increase the ratio of Bcl-2/Bax and reduce the expression of caspase-3 in the damaged cortex; increase the levels of nerve growth factor and brain-derived neurotrophic factor in the chronic phase; enhance the expression of synaptophysin I, synaptophysin, and postsynaptic density protein 95; inhibit brain trauma apoptosis regulation in the chronic phase [ 28 ]; and regulate the level of corticosterone [ 29 ] , all could play a neuroprotective effect . Molecular docking showed that telocinobufagin and beta-sitosterol, the active ingredients of Shan-Zhu-Yu, can act on NR3C1 , Bax , and Bcl-2 to treat depression.…”
Section: Discussionmentioning
confidence: 99%